العوامل الاجتماعية والسياسية المؤثرة في بناء ثقة المواطن المصري في وسائل الإعلام الراهن: دراسة سوسيولوجية - عمر، عبدالله حامد Omar, Abdullah Hamed (جامعة عين شمس - مركز بحوث الشرق الأوسط, 2022)
تقوم العلاقة بين الإعلام بوسائله المختلفة والمجتمع على أسس متبادلة، فكل منهما يؤثر في الآخر ويتأثر به. ويتضح ذلك جليا في عملية التنشئة الاجتماعية والسياسية للأفراد وتشكيل وعيهم في شتى المجالات. إشكالية البحث: لاحظ الباحث وجود حالة من عدم الرضا والثبات على الرأي بين المواطنين ممن بتعرض لهم في حياته اليومية على المنتج الإعلامي، وفي ضوء ذلك وما توفر للباحث من دراسات أجرى هذا البحث لتحديد العوامل الاجتماعية والسياسية المؤثرة في بناء ثقة المواطن المصري في وسائل الإعلام. أهمية البحث: تتحدد أهمية الدراسة في نوعين أساسيين: ١-الأهمية النظرية: وهي تطبيق محددات نظريتي البحث وهما: - نظرية الأثر الانتقائي لوسائل الإعلام. - نظرية الاعتماد المتبادل على وسائل الإعلام. ٢- الأهمية العملية: وهي تحديد عوامل بناء الثقة بين عنصري البحث. مجتمع العينة: تم اختيار مجتمع البحث من العاملين بمبنى الإذاعة والتلفزيون، حيث إنهم يمثلون صورة مصغرة من المجتمع. أدوات جمع البيانات اعتمد الباحث على تصميم واستخدام استمارة الاستبيان لجمع البيانات في هذه البحث. نوع ومنهج البحث: تعد هذه الدراسة من الدراسات الوصفية التي استخدمت منهج المسح الإعلامي الميداني. The relationship between the media, through its various means, and society, is based on mutual bases, as each affects and is affected by the other. This is evident in the process of social and political upbringing of individuals and the formation of their awareness in various fields. Research problem: The results of a survey conducted by the researcher on fifty random individuals of the community showed that the sample members disagreed on specific factors to build their confidence in the media, and in light of that and the studies provided to the researcher, this research was conducted. The importance of the research: the importance of the study is determined in two main types: 1- Theoretical importance: it is the application of the determinants of the two research theories namely: The theory of the selective impact of the media and the theory of interdependence on the media. 2- Practical importance: It is the identification of factors that build confidence between the two research components. Sample community: The research community was chosen from the employees of the radio and television building, as they represent a microcosm of the community. Data collection tools: The researcher relied on designing and using a questionnaire to collect data in this research. Type and method of research: This study is one of the descriptive studies that used the field media survey method.
Keywords: وسائل الإعلام -- العوامل الاجتماعية -- العوامل السياسية -- ثقة المواطنون -- المجتمع المصري